UPAYA MENINGKATAN KECERDASAN BAHASA MELALUI MODEL COOPERATIVE LEARNING PADA SISWA KELOMPOK B DI RA MUSLIMAT NU DESA KANDANG KECAMATAN COMAL KABUPATEN PEMALANG - Umaroh, Ms (Indonesian Journal of Early Childhood Education Studies, 2013)
Use of  Cooperative Learning Model in the implementation of  teaching and learning in Language In telligence Increase in RA Cage Muslimat NU Village District Comal Pemalang not been implemented optimally. This is because many teachers are still Muslimat NU RA Cage village who do notunderstand the importance of  learning models by using the Cooperative Learning Model. The method used in this study is the method of TOD study was conducted in two cycles, each cycle consisting of stages of plan- ning, action, observation, and ref lection. Data analysis was performed by analysis of quantitative data, an indicator of  the success of  all aspects of  the achievement of  each has a score of  90%. Based on the analysis of research data on the cycle I obtained the average value of 2.908 andcompleteness of students reached 65.4% of  student learning, student learning activities in the absence of  3%, the success of  the cooperation within the group 100%, 75% speak f luently, the richness of vocabulary word reached 59%, 50% expressed the idea, the ability to tell at 43%. Whereas in the second cycle reaches an average value of 3.254 and completeness reached 94% of student learning, student activity absences 0 with aspects of teamwork achievement of 100%, 91% speak f luently, the richness of vocabulary, 91%, 97% expressed the idea and the ability to tell 91 %. From this research, conclusions can be drawn is a learning cooperative learning model to improve intelligence. Suggestions for teachers to improve the intelligence of the langu- age you should use a learning model of cooperative learning, for schools to improve the management of teaching and learning activities to complement learning facilities to support the process of teaching and learning activities.